Accounting for goodwill under Vietnamese accounting practices, International financial reporting standards (IFRSs) and U.S. GAAP. - Trần, Đức Hiếu (2020)
Goodwill refers to “an asset representing the future economic benefits arising from other assets acquired in a business combination that are not individually identified and separately recognized” (Board, 2004, p.A152). Goodwill measures by amounts paid in excess of the fair value of the identifiable net assets for a business acquisition.Goodwill becomes a significant component of the balance sheet of many companies due to local and international mergers and acquisitions. For instance, goodwill has been reported as an increasingly significant component balance sheet asset in the US from 1990 to 2007 (Wen, 2016). In Vietnam, accounting for goodwill has first appeared in the accounting regulation under the Decision No 1141 TC/QĐ/CĐKT issued by the Ministry of Finance on01/11/1995 (Bui, 2017). This introduction has enabled Vietnamese companies to properly record new business transactions emerging in mergers and acquisitions that have been increasing after the economic reform (Thuy Ninh, 2016). Despite several changes, Vietnamese scholars have urged further amendments of goodwill accounting in hopes of providing more relevant and faithfully presented information to share holders and better harmonization to international accounting (Bui, 2017; Nguyen,2017). This becomes more important in the context of international integration because certain practices of accounting for goodwill may lead to disadvantages or advantages for companies in competing for international deals such as international bidding deals(Dune, 1992). Therefore, amendments of goodwill accounting should balance between international harmonization and effects of such amendments on Vietnamese companies.This study aims to shed a light on whether accounting for goodwill in Vietnam aligns with international accounting practices and its consequences on financial statements.Thus, the study focuses on the two questions: (1) What are differences between Vietnamese accounting for goodwill and international ones? And (2) what are consequences of the differences on the financial statements?In order to answer the aforementioned research questions, the case study is employed.Relevant Vietnamese accounting regulations and practices, International Financial Reporting Standards (IFRS) and Generally Accepted Accounting Principles (GAAP) inthe United State (US) are analysed.